2014
DOI: 10.1155/2014/890709
|View full text |Cite
|
Sign up to set email alerts
|

Novel Glycolipids Synthesized Using Plant Essential Oils and Their Application in Quorum Sensing Inhibition and as Antibiofilm Agents

Abstract: Essential oils (EOs) form an important part of traditional medicine so their anti-microbial and, in the recent past, antiquorum sensing activity has been well studied. However it is likely that due to their hydrophobic nature and reduced solubility in aqueous environments full potential of their activity cannot be realized. hence it is only rational to formulate a process to make these molecules more polar in nature. The present paper reports synthesis of sophorolipids using 12 different essential oils as subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…Our results indicate a significant correlation between the upregulation of the abaI gene and the augmentation of biofilm formation during the transition from planktonic to biofilm cells, suggesting a link between QS and biofilm formation in A. baumannii. Multidrug efflux pumps have been reported to have a central role in drug resistance, cell division, pathogenicity, and, in a recent report, QS signal secretion (39,40). In this study, the positive correlation observed between biofilm formation and upregulation of the adeB and adeG genes in A-IV-type A. baumannii and of adeG in A-III-type A. baumannii creates a link between the RND family of efflux pumps and A. baumannii biofilms.…”
Section: Discussionmentioning
confidence: 49%
“…Our results indicate a significant correlation between the upregulation of the abaI gene and the augmentation of biofilm formation during the transition from planktonic to biofilm cells, suggesting a link between QS and biofilm formation in A. baumannii. Multidrug efflux pumps have been reported to have a central role in drug resistance, cell division, pathogenicity, and, in a recent report, QS signal secretion (39,40). In this study, the positive correlation observed between biofilm formation and upregulation of the adeB and adeG genes in A-IV-type A. baumannii and of adeG in A-III-type A. baumannii creates a link between the RND family of efflux pumps and A. baumannii biofilms.…”
Section: Discussionmentioning
confidence: 49%
“…). Mukherji and Prabhune () reported antibiofilm activity of SL against Vibrio cholerae , indicating that it is likely to be broad spectrum. The morphological changes in microbial cells as a result of SL treatment (Haque et al .…”
Section: Inhibition Of Biofilm Formationmentioning
confidence: 99%
“…Previously, numerous studies have shown that biosurfactants inhibit biofilm formation by preventing adhesion of micro-organisms to solid surfaces (Kuiper et al 2004;Rodrigues et al 2004;Rivardo et al 2009;Janek et al 2012). Mukherji and Prabhune (2014) reported antibiofilm activity of SL against Vibrio cholerae, indicating that it is likely to be broad spectrum. The morphological changes in microbial cells as a result of SL treatment (Haque et al 2016) may go some way towards explaining the broad-spectrum nature of SLs and other biosurfactants (Haque et al 2016).…”
Section: Inhibition Of Biofilm Formationmentioning
confidence: 99%
“…This produces sophorolipids that inhibit biofilms of V. cholerae (Mukherji and Prabhune 2014). Other strains of yeast such as Candida sphaerica have also been reported to produce biosurfactants such as Iunasan ).…”
Section: Biosurfactants From Fungimentioning
confidence: 99%